2021
DOI: 10.7547/20-166
|View full text |Cite
|
Sign up to set email alerts
|

Dosing Activity and Return to Preulcer Function in Diabetes-Related Foot Ulcer Remission

Abstract: Diabetes-related foot ulcers are a leading cause of global morbidity, mortality and healthcare costs. People with a history of foot ulcers have a diminished quality of life attributed to limited walking and mobility, decreased moderate intensity exercise when compared to people with diabetes without ulcers. One of the largest concerns is ulceration recurrence. Approximately 40% of patients with ulcerations will have a recurrent ulcer in the year following healing and the majority occurs in the first three mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Based on 8 studies with 291 participants, 25,27,[36][37][38]41,42,46 we found a mean (over the total number of included studies) of 6167 steps per day (range: 4548 to 8450) in people at high risk of ulceration (IWGDF risk 3); the weighted mean, over the total number of participants included in these studies, was 6239 steps. Finally, based on 6 studies with 186 participants, [20][21][22]25,43,47 we found a mean (over the total number of included studies) of 4248 steps per day (range: 1219 to 8153) in people with a foot ulcer; the weighted mean, over the total number of participants included in these studies, was 4484 steps.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Based on 8 studies with 291 participants, 25,27,[36][37][38]41,42,46 we found a mean (over the total number of included studies) of 6167 steps per day (range: 4548 to 8450) in people at high risk of ulceration (IWGDF risk 3); the weighted mean, over the total number of participants included in these studies, was 6239 steps. Finally, based on 6 studies with 186 participants, [20][21][22]25,43,47 we found a mean (over the total number of included studies) of 4248 steps per day (range: 1219 to 8153) in people with a foot ulcer; the weighted mean, over the total number of participants included in these studies, was 4484 steps.…”
Section: Resultsmentioning
confidence: 84%
“…Reference checking resulted in an additional 3 publications, giving a total 27 publications from 21 studies. 14,[19][20][21][22][23][24][25][26][27][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] In one publication, outcomes were reported as part of a guideline, yet without population characteristics. 47 We contacted the first author, who confirmed the correctness of the data and confirmed data was obtained from a subset of which population data were published elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…However, we do note that as recommended in the accompanying Australian guideline to prevent DFU there is moderate quality of supporting evidence for the use of medical grade footwear to prevent recurrence of DFU once healed [39]. Thus, we suggest that health professionals strongly consider arrangements to transition into medical grade footwear when healing is (nearly) achieved as per expert consensus guidelines [50] and refer the reader to the accompanying Australian guideline to prevent DFU [39]. Finally, while there is no literature to support their use as treatment to heal people with DFU, wheelchairs, knee scooters or electric scooters may be considered in these rare circumstances.…”
Section: Implementation Considerations For Effective Implementation W...mentioning
confidence: 80%
“…Reports by the investigators found that patients optimally received one alert every 2 h, and a reduction of DFU recurrence was associated with the use of this smart sensor technology [ 276 , 277 ]. Recent guidelines for DFU prevention have incorporated regular monitoring of foot skin temperature to assess for early signs of inflammation and enable early intervention to prevent ulceration [ 278 ]. A number of other wearable devices have been created for thermal foot monitoring, including smart insole systems [ 279 , 280 ] and socks [ 281 , 282 ], though the efficacy of these wearables in DFU prevention or wound-healing monitoring need to be further tested.…”
Section: Diagnostic Measuresmentioning
confidence: 99%